Strategi Meningkatkan Kinerja UMKM Melalui Kesadaran Halal di Kalangan Pelaku Usaha - Ni Putu Mas Aswameda Yadnya Nusantara; Eka Mariyanti; Firman syakri pribadi (CV. ITTC INDONESIA, 2024)
This study aims to ascertain the influence of halal awareness and entrepreneurial motivation on the performance of MSMEs in Padang City. A survey methodology was employed, with questionnaires distributed to 137 respondents, selected through the use of a purposive sampling technique. The sample size was determined with the assistance of the Raosoft Sample Size Calculator. Subsequently, the data were processed and tested using the Statistical Package for the Social Sciences (SPSS) version 21 to test the aforementioned hypothesis. The findings revealed that, of the two independent variables under investigation, namely halal awareness and entrepreneurial motivation, the variable of halal awareness exerted a more pronounced influence on the performance of MSMEs in Padang City. This is indicated by a beta value of 0.408, which suggests that an increase in halal awareness among MSME players can lead to a notable enhancement in their business performance. It is therefore recommended that MSME players in Padang City develop a deeper understanding of and implement the concept of halal awareness in their business operations. This may be achieved by registering their products for halal certification, ensuring that the production process meets halal standards, and maintaining the cleanliness and hygiene of the production site. It is important to note that not all clean products are necessarily halal. Rather, products that are halal must adhere to specific hygiene standards. Therefore, businesses must ensure that every stage of production meets these standards to increase consumer confidence. Furthermore, it is crucial for MSME players to participate in training or workshops pertaining to halal principles and production management in accordance with halal standards. In order to enhance the performance of MSMEs, businesses are advised to not only prioritize halal awareness, but also to consider other factors that can contribute to their performance, such as entrepreneurial competency development, enhanced human resource management, and more effective marketing strategies.